Water allocation under climate change: A diagnosis of the Chilean system - Barria, Pilar; Barria Sandoval, Ignacio; Guzman, Carlos; Chadwick, Cristian; Alvarez-Garreton, Camila; Diaz-Vasconcellos, Raul; Ocampo-Melgar, Anahi; Fuster, Rodrigo (My University, 2021)
Chile is positioned in the 20th rank of water availability per capita. Nonetheless, water security levels vary across the territory. Around 70% of the national population lives in arid and semiarid regions, where a persistent drought has been experienced over the last decade. This has led to water security problems including water shortages. The water allocation and trading system in Chile is based on a water use rights (WURs) market, with limited regulatory and supervisory mechanisms, where the volume to be granted as permanent and eventual WURs is calculated from statistical analyses of historical streamflow records if available, or from empirical estimations if they are not. This computation of WURs does not consider the nonstationarity of hydrological processes nor climatic projections. This study presents the first large sample diagnosis of water allocation system in Chile under climate change scenarios. This is based on novel anthropic intervention indices (IAI), which were computed as the ratio between the total granted water volume to the water availability within 87 basins in north-central and southern Chile (30 degrees S-42 degrees S).The IAI were evaluated for the historical period (1979-2019) and under modeled-based climatic projections (2055-2080). According to these IAI levels, to date, there are 20 out of 87 overallocated basins, which under the assumption that no further WURs will be granted in the future, increases up to 25 basins for the 2055-2080 period. The results show that, to date most of north-central Chilean catchments already have a large anthropic intervention degree, and the increases for the future period occurs mostly in the southern region of the country (approximately 38 degrees S), which has been considered as possible source of water for large water transfer projects (i.e., water roads). These indices and diagnosis are proposed as a tool to help policy makers to address water scarcity under climate change.
Keywords: water management; water market; climate change; hydrological modeling